Strategy Analysis: Fancy Feet Running Gear - Cooper, Joy; Davis, Larry (American Journal of Management, 2021)
This paper analyzes the target market responses and product offerings of organization strategy decisions of a small specialty retail company. A survey was conducted, and results were analyzed and presented based on the strategies as presented in The Discipline of Market Leaders: Choose Your Customers, Narrow Your Focus, Dominate Your Market (Treacy & Wiersema, 1995). The paper navigates through the external and internal change process considerations that impact the operation of a specialty retail business within a fluid retail market in a rural geographical environment. The research provided a view of owner, employee, and customer perspectives related to the store. Employees expressed the ability to be creative, conduct research and have a level of autonomy. It also showed that operational excellence is not the highest ranked element and that shoppers are attached to the convenience of local shopping. The store appeared to recognize emerging needs of the target market and assess customer response to the organization’s strategic decisions.